2015
DOI: 10.1038/onc.2015.238
|View full text |Cite
|
Sign up to set email alerts
|

Translational regulation of inhibin βA by TGFβ via the RNA-binding protein hnRNP E1 enhances the invasiveness of epithelial-to-mesenchymal transitioned cells

Abstract: The epithelial-to-mesenchymal transition (EMT) is a cellular process that functions during embryonic development and tissue regeneration, thought to be aberrantly activated in epithelial-derived cancer and play an important role in the process of metastasis. The TGFβ signaling pathway is a key inducer of EMT and we have elucidated a post-transcriptional mechanism by which TGFβ modulates expression of select transcripts via the RNA binding protein hnRNP E1 during EMT. One such transcript inhibin βA is a member … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…A variant of the normal murine mammary gland epithelial cell line (NMuMG*), in which an RNA-binding protein hnRNPE1 is knocked down by RNA interference, was recently described as being capable of forming tumors in nude mice (38). Intriguingly, we found these cells expressed a significantly high level of endogenous GARP (Figure 1D–1F), raising the possibility that increased GARP expression, in addition to the silencing of the TGF-β-mediated translation repression complex, drives mammary cancer in this model.…”
Section: Resultsmentioning
confidence: 99%
“…A variant of the normal murine mammary gland epithelial cell line (NMuMG*), in which an RNA-binding protein hnRNPE1 is knocked down by RNA interference, was recently described as being capable of forming tumors in nude mice (38). Intriguingly, we found these cells expressed a significantly high level of endogenous GARP (Figure 1D–1F), raising the possibility that increased GARP expression, in addition to the silencing of the TGF-β-mediated translation repression complex, drives mammary cancer in this model.…”
Section: Resultsmentioning
confidence: 99%
“…Altering the expression profile of specific mRNA targets inhibits the process of metastasis [22, 23, 47]. Similar to the control of mRNAs responsible for the transition of cancer cells, it has been shown that incorrect processing, delivery and regulation of mRNAs can be the cause of human neurological diseases [53].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that KLF4 also displayed a distinct regulatory profile (Fig. 6E), we selected INHBA, which encodes the inhibin beta A subunit, a member of the TGFβ signalling pathway (Howley et al, 2016). INHBA was upregulated upon KLF4 overexpression in chMM cultures (Fig.…”
Section: Validation Of Selected Target Genesmentioning
confidence: 99%